Penguatan Nilai-Nilai Toleransi Melalui Pembelajaran Pendidikan Agama Islam ( PAI ) di SMKs 6 Pertiwi Curup - Rasmini Rasmini; Fakhruddin; Sumarto Sumarto (Jurnal Pendidikan Guru, 2023)
Islamic Religious Education emphasizes the position of morality including respecting others or tolerance which greatly influences a person's behavior. The subject of Islamic religious education (PAI) is one of the intracurricular learning, namely as a support in realizing the values ??of tolerance through learning. This type of research is qualitative with a descriptive approach. Data sources were obtained from the results of observations of the school environment, interviews, with school principals, vice curricula, Islamic religious education teachers, Muslim students and non-Muslim students and documentation. Data collection techniques in this study were observation, interviews and documentation. Data analysis techniques used is data reduction, data display, conclusion and verification. This research concludes that the learning of Islamic religious education that is carried out is to form a Muslim personality, namely a personality whose all aspects are imbued with Islamic teachings. There are values ??in tolerant education that need to be developed in the world of education, learning in differences, building mutual trust, maintaining mutual understanding, upholding mutual respect. The basic values ??of tolerance that are applied are based on the values ??of Pancasila, Culture, Religion and National Education Goals. The application of strengthening the values ??of tolerance at SMKs 6 Motherland Curup has been well implemented. The tolerance that is applied is to be open-minded, respect, understand each other, and allow someone to have different beliefs, such as in terms of religion, in terms of culture, and respecting one's stance, respecting the opinions of others.